An Experimental Study on Electrochemical Grinding Parameters on Hardness and Material Removal Rate for Stainless Steel 316 - Ghadban, Abdullah J.; Ibrahim, Abbas F. (Al-Khwarizmi Engineering Journal, 2019)
Electrochemical Grinding (ECG) process is a mechanically assisted electrochemical process for material processing. The process is able to successfully machine electrically conducting harder materials at faster rate with improved surface finish and dimensional control. This research studies the effect of applied current, electrolyte concentration, spindle speed and the gap between workpiece and tool on hardness and material removal rate during electrochemical grinding for stainless steel 316. The characteristic features of the electrochemical grinding process are explored through Taguchi-design-based experimental studies. The better hardness can be obtained at 10 A of the current, 150 g/l of the electrolyte concentration, 0.3 mm of gap and spindle speed of 180 rpm, and the maximum material removal rate can be obtained at 40 A of the current, 250 g/l of the concentration, 0.2 mm of a gap and 180 rpm of spindle speed.